Satisfaction of an employee in a sports entity: design and validation of a measurement scale - Reyes Robles, Marina; Medina Rodríguez, Rosa Elena; Ramírez Siqueiros, María Grethel; López Walle, Jeanette M.; Ceballos Gurrola, Oswaldo (2018)
This research aims to generate validation and reliability of an instrument to measure employee satisfaction in a sports entity, comprising 28 items in six factors, using a Lickert type measure. The sample comprises n = 187 employees of the State Sports Commission of Sonora, Mexico, with 75.4% men and 24.6% women, between the ages of 18 to 56 years, grouping the different ages of workers in five groups (18 to 25 years, 26 to 35 years, 36 to 45 years, 46 to 55 years and > 56 years. Carrying out the exploratory factor analysis (AFE) and confirmatory factor analysis (AFC). Satisfactory values were obtained, resulting in Kaiser-Meyer-Olkin values of .91, and the Bartlett test was statistically significant with a value (χ² = 3296.01, gl = 378; p <. 001), six factors were extracted with eigen values greater than 1 and that together explain 69.08% of the total variance. the indices of the model in the confirmatory factor analysis were satisfactory: χ2 / df = 1.29, NNFI = .99, CFI = .99, and RMSEA = .03., The results of internal consistency using Cronbach's alpha index with values in this case greater than .70, composite reliability (CR) with values between .88 and .94, and the average variance index extracted (AVE), meanwhile, alsoshowed adequate values, in a range between .60 and .83. It is considered that the survey of employee satisfaction was statistically validated, obtaining psychometric guarantees and thereby providing a tool for the evaluation of the subject, accrediting it as useful for research, being able to be used by professionals, managers and those responsible within the different organizations.